An empirical study of aspect-oriented metrics - Piveta, Eduardo Kessler; Moreira, Ana; Pimenta, Marcelo Soares; Araújo, João; Guerreiro, Pedro; Price, R. Tom (Science of computer programming, 2012)
Metrics for aspect-oriented software have been proposed and used to investigate the benefits and the disadvantages of crosscutting concerns modularisation. Some of these metrics have not been rigorously defined nor analytically evaluated. Also, there are few empirical data showing typical values of these metrics in aspect-oriented software. In this paper, we provide rigorous definitions, usage guidelines, analytical evaluation, and empirical data from ten open source projects, determining the value of six metrics for aspect-oriented software (lines of code, weighted operations in module, depth of inheritance tree, number of children, crosscutting degree of an aspect, and coupling on advice execution). We discuss how each of these metrics can be used to identify shortcomings in existing aspect-oriented software.